ANALISIS EKSISTENSI TANAH AYAHAN DESA ADAT DIBALI DI TINJAU DARI UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR-DASAR POKOK AGRARIA (STUDI KASUS: DESA TUSAN, KECAMATAN BANJARANGKAN, KABUPATEN KLUNGKUNG, BALI) - Regina Regina; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
In Indonesia there are still customary rights, customary rights are the oldest rights of customary law communities whose existence is recognized in Article 3 of Law Number 5/1960 as long as the reality still exists and does not conflict with national interests. one of the objects of customary rights is customary land. The existence of customary community's customary land is spread throughout Indonesia, including Bali. Bali is still very strong in customs and culture so that it has many customary law communities who have customary land in each region in Bali. one of them is AYDS land which is located in the Tusan village area, banjarangkan sub-district, klungkung regency, bali. is land that cannot be bought and cannot be certified because it is land with the community in Tusan Village. but someone named I Ketut Sotong said that he had a certificate of ownership of the land which at the time the land was occupied by Ni Wayan Rosih who was a resident of Tusan village. therefore this research uses a type of normative legal research methods with a legal approach. This research will examine further the existence of customary land namely AYDS in terms of law number 5 of 1960.